Improved stability and transshipment of enzymatic hydrolysate with ACE inhibitory activity‐loaded nanogels based on glycosylated soybean protein isolate via the Maillard reaction. (24th May 2021) - Cui, Tingting; Jia, Airong; Shi, Yaping; Zhang, Miansong; Bai, Xinfeng; Liu, Xue; Sun, Jimin; Liu, Changheng
Summary: In this study, soybean protein isolate (SPI)‐konjac glucomannan (KGM) conjugates were fabricated via the Maillard reaction and their potential to improve enzymatic hydrolysate with ACE inhibitory activity stability was assessed. Briefly, we loaded the enzymatic hydrolysate into SPI‐KGM conjugates using a pH‐driven method. Thereafter, the transport pathway of enzymatic hydrolysate with angiotensin‐converting enzyme (ACE) inhibitory activity SPI‐KGM (ACE‐SPI‐KGM) core–shell nanogels was investigated using CaCo‐2 cell monolayer. The results of microstructure, encapsulation efficiency, ACE inhibition ratio and IC50 value verified that the nanogels displayed a spherical structure and excellent physicochemical properties. The ζ‐potential, Z‐average diameter and polydispersity index demonstrated that the stability of the core–shell nanogels was significantly superior to that of the enzymatic hydrolysate. In addition, the transport of the enzymatic hydrolysate in nanogels onto the CaCo‐2 cell monolayer revealed a higher transport capacity and was dominated by cell bypass transport. In summary, the SPI‐KGM conjugates could serve as potential as delivery systems for enzymatic hydrolysate with ACE inhibitory activity to fortify functional foods and medicines. Abstract : The physicochemical characteristics, microstructure, and transport pathway on CaCo‐2 cells monolayer of nanogels formed using the self‐assembly of konjac glucomannan (KGM)‐soy protein isolate (SPI) conjugates and loaded with ACE inhibitory peptide into conjugates by a pH‐driven method.